Effect of phase composition on protein adsorption and osteoinduction of porous calcium phosphate ceramics in mice. Issue 12 (11th February 2014) - Wang, Jing; Chen, Ying; Zhu, Xiangdong; Yuan, Tun; Tan, Yanfei; Fan, Yujiang; Zhang, Xingdong
Abstract The purpose of this study was to investigate the effect of phase compositions of porous calcium phosphate (CaP) ceramics on their protein adsorption behaviors in vitro and osteoinductive potentials in vivo in mice. Under competitive conditions, a high adsorption of bone morphogenetic protein 2 (BMP‐2) was observed at a high initial concentration of BMP‐2 in the multi‐protein solution on all the four types of ceramics, indicating their strong affinity for BMP‐2. No significant difference in BMP‐2 adsorption between the ceramics was noted, indicating that phase composition could have little influence on BMP‐2 adsorption. After implantation into the thigh muscles of mice for 45 and 90 days, the histological and histomorphometric analyses showed that porous biphasic calcium phosphate (BCP) ceramic consisting of 30% hydroxyapatite HA and 70% tricalcium phosphate (β‐TCP), i.e. BCP‐2 had stronger osteoinductive ability than the other three groups of ceramics. The immunohistochemical staining showed the highest expression of BMP‐2 and osteocalcin (OCN) in BCP‐2 group. Osteoinduction of porous CaP ceramics might be influenced by the amount of BMP‐2 present in the local microenvironment in the implant, which was regulated by the phase composition of the ceramics. BCP‐2 promoted the highest expression of BMP‐2 and then showed the strongest osteoinduction in mice. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4234–4243, 2014.